Atividade metaloproteinases e propriedades físicas, químicas e biomecânicas de ossos de ratos tratados com cloreto de mercúrio - Dávila, Fernando Vidal (2011)
There are few data about the mercury influence on bone metabolism them it is important to investigate the bone parameters that can be affected by it. The aim of this study was to evaluate the biometric, physical, biomechanical and enzymatic (MMPs) bone alterations in adult rats contaminated with mercurous chloride (HgCl2) during their development. The animals were separated in 4 groups: 3, 6, 9 and 12 months. The animals received mercuric chloride (experimental group) and saline (control group) by stomach gavage. The treatment had begun on 30 days of animals life, 5 times a week during 60 days. The daily dose was 5mg/kg of body weight of HgCl2 and 0,1ml of saline /100g of body weight. The animals were weighted 3 times a week until the sacrifice day. After the period of contamination, the 3 months groups were sacrificed, while the other groups stayed without treatment to complete their ages (6, 9 and 12 months). The animals femurs, tibia and vertebras (L5) were dissected to be analyzed on biometric, biomechanical and enzymatic parameters. To statistical analyze it was used the normality test Shapiro-Wilk, the variance tes Two-way analysis (ANOVA) (for time and treatment), and the Tukey Test to do multiple comparisons using Graphpad Instat (version 3.00 December 1997). All the values were expressed as media ± standard error media and the significance level was p ≤ 0.05. There was a tendency of a percent increase of mineral material, mineral and bone density and of the maximum force of femurs sample on contaminated groups related to their respective controls. The contaminated animals showed difference on the maximum force of the vertebras, which the 6 months had a higher value than the 3 months group. It was higher MMP-2 activity on mercury group than on the saline group with the same age. The results showed that the HgCl2 on 5m/Kg dose, when related to the control group, did not present difference of biometric, biophysical and biomechanical parameters on bone tissue of rats in development. The HgCl2 contamination stimulated the MMP-2 activity at the end of the contamination period and remained until 6 months after the contamination.